CULTURE-ANTHROPOLOGICAL PURPOSE OF THE DOCUMENT IN MODERN CONDITIONS - Абрамова, Эльвира (SWorldJournal, 2021)
The paper considers the document as a subject of human understanding in modern society. The author reveals the main points of interpretation of the document, focusing on the forms of fixing the document in historical terms. He speaks of physical media inv